Anticonvulsants and the risk of perinatal bleeding complications: A pregnancy cohort study. (7th August 2018) - Panchaud, Alice; Cohen, Jacqueline M.; Patorno, Elisabetta; Huybrechts, Krista F.; Desai, Rishi J.; Gray, Kathryn J.; Mogun, Helen; Hernandez-Diaz, Sonia; Bateman, Brian T.
Abstract : Objective: To examine the risk of postpartum hemorrhage (PPH) and neonatal bleeding complications associated with late-pregnancy exposure to anticonvulsant drugs (ACDs) that induce cytochrome P450 enzymes (ACDi) and alter the metabolism of vitamin K compared to other ACDs. Methods: We used a population-based cohort study stemming from a nationwide sample of publicly insured pregnant women with a liveborn infant from the 2000 to 2010 Medicaid Analytic eXtract. ACDi (carbamazepine, phenobarbital, phenytoin, oxcarbazepine, topiramate) were compared to other ACDs dispensed during the last month of pregnancy. Relative risks (RRs) and 95% confidence intervals (CIs) of PPH and neonatal bleeding complications were estimated using generalized linear models with fine stratification on the propensity score to control for indication and other potential confounders. Results: Among 11, 572 women with an ACD prescription overlapping delivery, 2.6% (135/5, 109) in the ACDi group and 3.6% (231/6, 463) in the other ACDs group had a diagnosis of PPH: unadjusted RR 0.74 (95% CI 0.60–0.91), adjusted RR 0.77 (95% CI 0.58–1.00). The prevalence of neonatal bleeding complications was 3.1% (157/5, 109) in the ACDi group and 3.5% (229/6, 463) in the other ACDs group: unadjusted RR 0.87 (95% CI 0.71–1.06), adjusted RR 0.83 (95% CI 0.64–1.08). Conclusions: Evidence from this large observational study suggests that use of ACDi near delivery does not increase the risk of bleeding complications compared to other ACDs in clinical settings where neonatal intramuscular or oral vitamin K administration is considered standard of care. These findings provide reassurance for clinicians and pregnant women successfully treated with ACDi.